1999
DOI: 10.1038/sj.bmt.1701610
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenic infections in 100 patients with non-Hodgkin’s lymphoma or Hodgkin’s disease treated with high-dose BEAM chemotherapy and peripheral blood progenitor cell transplant: out-patient treatment is a viable option

Abstract: Summary:A retrospective analysis was performed on 100 patients with non-Hodgkin's lymphoma (NHL, n = 75) or Hodgkin's disease (HD, n = 25) who underwent peripheral blood progenitor cell transplant (PBPCT) following high-dose chemotherapy (HDCT) with BCNU, etoposide, cytarabine and melphalan (BEAM) between March 1994 and June 1997. Following PBPCT and until engraftment all patients received oral ciprofloxacin and fluconazole, patients with positive Herpes simplex virus serology received acyclovir and 91 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 17 publications
0
20
1
2
Order By: Relevance
“…Comparative studies including this report have demonstrated the safety of this approach and significant cost-savings, particularly among standard risk patients. [2][3][4][5][6][7][8][9] Whereas the majority of prior studies have measured direct medical costs, we also studied indirect costs to the caregiver including lost 'opportunity costs' and out-of-pocket expenses. At our institution, outpatient transplantation was associated with approximately $14 000 in savings in direct medical costs, without any decrement in quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative studies including this report have demonstrated the safety of this approach and significant cost-savings, particularly among standard risk patients. [2][3][4][5][6][7][8][9] Whereas the majority of prior studies have measured direct medical costs, we also studied indirect costs to the caregiver including lost 'opportunity costs' and out-of-pocket expenses. At our institution, outpatient transplantation was associated with approximately $14 000 in savings in direct medical costs, without any decrement in quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…1 A growing number of studies have demonstrated reductions in the length of hospital stay without compromising outcome. [2][3][4][5][6][7][8] A reduction in direct medical costs for outpatient HSCT has been demonstrated in some series, fueling enthusiasm for this approach. 2,4,7,9,10 There is little information, however, on the total costs of transplantation including nonmedical and out-of-pocket costs.…”
mentioning
confidence: 99%
“…These results are in line with previously reported data on infections in bone marrow transplant recipients. 16,17 Multivariate analysis identified a group of patients conditioned with a single alkylating agent-containing regimen and with no or mild mucositis, that had a lower probability of developing fever. The number of alkylating agents did not influence the duration of profound neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true in very select instances for patients undergoing allogeneic transplants. [2][3][4][5][6][7][8] This shift of care has also occurred owing to improvements in supportive care, as well as cost and quality of life (QOL) issues. The main drivers of this change were the use of peripheral blood rather than bone marrow stem cells, and improvements in supportive care (i.e., antibiotic algorithms, antiemetic regimens and transfusion protocols).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of less mucotoxic preparative regimens, approximately 10 years ago several groups began to explore the feasibility of performing HSCT at least partially on an outpatient basis. [1][2][3][4][5][6][7][8] The initial strategy was to administer the preparative regimen in the outpatient setting with subsequent admission for follow-up care for patients diagnosed with breast cancer. More recently, select patients diagnosed with lymphoma and multiple myeloma have been successfully autotransplanted completely in the outpatient setting, utilizing non-total body irradiation (TBI)-based regimens.…”
Section: Introductionmentioning
confidence: 99%